1970
DOI: 10.3329/jbau.v7i2.4752
|View full text |Cite
|
Sign up to set email alerts
|

Broiler farming: An approach to improve rural livelihood

Abstract: The present study assessed the changes in socio-economic conditions of small scale broiler farmers in rural areas of Bangladesh. The population comprised the small scale broiler farmers who reared at least 300 to less than 2000 birds in the rural areas of Sadar Upazila of Mymensingh district, among which a total of 50 samples were randomly selected for the study. The necessary data on different socio-economic parameters were collected from the respondents through personal interview with the pre-tested intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…A look into Table 10 reveals that majority of the respondents (66%) had medium size (300-1,000 birds) followed by small size (25%, 100-300 birds) and large size (9%, 1,000 and above birds) flock. Mozumdar et al (2009) found that small broiler farmers (300-2,000 birds) dominated the rural areas of Mymensingh in Bangladesh. Flock size of 300-1,000 birds was very less in comparison to other states of India.…”
Section: Flock Sizementioning
confidence: 99%
See 2 more Smart Citations
“…A look into Table 10 reveals that majority of the respondents (66%) had medium size (300-1,000 birds) followed by small size (25%, 100-300 birds) and large size (9%, 1,000 and above birds) flock. Mozumdar et al (2009) found that small broiler farmers (300-2,000 birds) dominated the rural areas of Mymensingh in Bangladesh. Flock size of 300-1,000 birds was very less in comparison to other states of India.…”
Section: Flock Sizementioning
confidence: 99%
“…Occupation Table 6 reveals that majority of the farmers were agriculturists (35%) in occupation followed by broiler farmers (27%), government servant (20%), non-agricultural labourers (11%) and craftsmen (7%). Mozumdar et al (2009) reported that 46% respondents were crop producers, 34% broiler farmers, 8% service holders and 12% businessmen, fishermen and others. However, Gogoi (2004) found that 40% of the respondents were service holders, 30% were businessmen and 20% were farmers.…”
Section: Family Typementioning
confidence: 99%
See 1 more Smart Citation
“…A look into Table 1 reveals that majority of the respondents (66%) had medium size (300-1,000 birds) followed by small size (25%, 100-300 birds) and large size (9%, 1,000 and above birds) flock. Mozumdar et al (2009) found that small broiler farmers (300-2,000 birds) dominated the rural areas of Mymensingh in Bangladesh. Flock size of 300-1,000 birds was very less in comparison to other states of India.…”
Section: Flock Sizementioning
confidence: 99%
“…Final rank order of the selected problems was done based on total weighted score of each problem. Total score was determined by the formula followed by Mozumdar et al (2009). The formula is given below.…”
Section: Ranking the Constraints To Duck Farmingmentioning
confidence: 99%